Manajemen Pemerintahan Daerah Dalam Pelayanan Publik (Studi Pengelolaan Lampu Penerangan Jalan di Kota Pekanbaru Tahun 2012) - M. FAJAR ANUGERAH; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Public service is an attempt to meet the basic needs of the state and the civil rightsof every citizen in the goods, services, and administrative services provided by publicservice providers. Road which is one form of government services to the community is veryimportant to note, from the complementary parts, one of which is a public street lightinghas not been felt their effectiveness for road users, especially at night.This study aims to determine the management of the regional government in themanagement of public street lighting by the Department of Hygiene and Pekanbaru Cityand to determine the factors that influence the management of the public street lighting.Using resources through informants. In this study, the informant was a member ofCommission II DPRD Pekanbaru, Head of Parks and Street Lighting, Street LightingSection Head and Head of PLN branch of Pekanbaru. While the techniques of datacollection consisted of interviews , documentation and observation with the source dataconsists of primary data and secondary data.From the results of the study showed that the management of the regionalgovernment in the management of public street lighting by the Department of Hygiene andPekanbaru to the process of planning, organizing, implementing , coordinating andmonitoring has not gone up . The factors that influence in the management of public streetlighting consists of human resources and infrastructure, the participation of thecommunity , traffic congestion.Keywords :Management, Public service, Light Manajement